2019
DOI: 10.2106/jbjs.oa.19.00004
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Pseudarthrosis of the Tibia

Abstract: Background: This study assessed the outcomes, at skeletal maturity, for 34 patients in whom congenital pseudarthrosis of the tibia (CPT) had been treated with intramedullary (IM) rod fixation. Methods: The results in skeletally mature patients in whom type-4 CPT had been treated with an IM rod at an average of 11.9 years earlier were reviewed. The rod procedures varied according to whether both the tibia and the fibula were resected and both bones (type A) or just the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Association with NF1 is considered to be a negative predictor for bone union, refractures and final outcome in CPT by certain studies [46,60,62,65,66]. However, others have reported no effect on final results with comparable rates of union in NF and non-NF groups [13,18,24,26,27,30,46,52,53,60,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Association with NF1 is considered to be a negative predictor for bone union, refractures and final outcome in CPT by certain studies [46,60,62,65,66]. However, others have reported no effect on final results with comparable rates of union in NF and non-NF groups [13,18,24,26,27,30,46,52,53,60,64].…”
Section: Discussionmentioning
confidence: 99%
“…The following information was extracted and recorded into excel sheets: number of patients/tibias with CPT, number of patients/fibulas with fibular pseudarthrosis (FPA), presence/absence of NF1, mean age at surgery (years), mean duration of follow-up, type of surgical intervention, type of union, mean time to union (months), number of non-unions, number of refractures, bone graft (BG) source and adjuvants used (Tables 1–5) [1–57]. The type of union was categorized as primary (cases which united after index surgery), secondary (cases requiring additional intervention after index surgery for union) and final (overall unions including primary and secondary unions).…”
Section: Methodsmentioning
confidence: 99%
“…Dustin Singer et al . [10] reported that 34 children with CPT were treated with the intramedullary rod, with an average follow-up of 11.9 years. Although 13 cases had re-fracture (38%), most of them obtained tibial pseudarthrosis healing through bone grafting and other operations.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of congenital pseudarthrosis of the tibia (CPT) is unknown [1], which is one of the refractory diseases in children's orthopedics [2][3][4][5][6][7][8][9][10]. With the improvement of surgical technology, the healing rate of CPT has improved significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Type of surgery to achieve union and prevent refracture remains controversial. Initial management is resection of entire pseudoarthrosis and surrounding hamartomatous tissue [6] . Atrophic type of CPT is more challenging.…”
Section: Outcome Of Congenital Pseudoarthrosis Tibia Treated With Illmentioning
confidence: 99%